THE PROTECTION OF WOMEN IN ARMED CONFLICT - Bunga, Gerald Aldytia (Yustisia, 2017)
The vulnerable groups often become the victim of adverse party of armed conflict. Women is included in there. Women in armed conflict are affected directly or indirectly by the conflict, including gender based violence like rape, forced impregnation, or forced prostitution. In addition, armed conflict also affects the gender relation related to women, for example women become the breadwinner as the result of lost of husband due to the conflict. this research aimed to discuss on the impact of armed conflict on women, how international humanitarian law protects women in armed conflict and how the implementation of that protection.